Revision of the genus Macropsobrycon Eigenmann, 1915 (Characidae: Cheirodontinae: Compsurini) - Jerep,Fernando C. (2011)
The cheirodontine genus Macropsobrycon is redefined and considered monotypic. The type species, M. uruguayanae, is redescribed based on samples from the entire known geographical distribution of the species. Sexually dimorphic characters of M. uruguayanae are further described and the relationships of the species with the remaining Compsurini are discussed.